(3eNJUQ JGQjN OeTb dGHf YSGcQs - (3eMeO Hf ecQe Hf Ydj, CHh GdaVd, LeGd GdOjf GHf efXhQ GdCfUGQj GdQhjaYj GdEaQjbj, J (B711 (3g` s; (3Ydj Hf GdMSf Hf gHI Gddg GdOeTbj , CHh GdbGSe, KbI GdOjf GHf YSGcQ,J (B600 (3g` s ((3CHhYHOGddg eMeO Hf GdecQe Hf CHj GdMSfi Hf CHj GdbGSe GdCfUGQi GdcGJH s)
(3ChdgG (B:s
(3djHJOF HHGH UaI Ndbg heYQaI Ndbg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3jfJgi Edi PcQ eG CYOg Gddg ef GdKhGH def jUdi Ydjg s
(3eUhQI Yf fSNI chHQjdi Qbe (B1148 (3HGdCSJGfIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJGQjNs